2022
DOI: 10.1186/s12885-022-09384-9
|View full text |Cite
|
Sign up to set email alerts
|

Octogenarian patients with colon cancer – postoperative morbidity and mortality are the major challenges

Abstract: Background Few studies have addressed colon cancer surgery outcomes in an unselected cohort of octogenarian patients. The present study aimed to evaluate the relative survival of octogenarian patients after a major resection of colon cancer with a curative intent. Methods All patients diagnosed with colon cancer at Levanger Hospital between 1980 and 2016 were included. We performed logistic regression to test for associations between 90-day mortali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
4
5
0
Order By: Relevance
“…Similar to previous studies [35][36][37], we demonstrated that postoperative complications have a negative impact on OS in all study subgroups. In accordance with our findings, a study from Norway reported higher 90-day mortality rates in octogenarian patients as well as an association with poorer 5-year survival rates [38]. Consequently, to improve long-term survival after colorectal cancer surgery future research should focus on the first 90 days after surgery, as our study indicates that this period of risk is potentially modifiable.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies [35][36][37], we demonstrated that postoperative complications have a negative impact on OS in all study subgroups. In accordance with our findings, a study from Norway reported higher 90-day mortality rates in octogenarian patients as well as an association with poorer 5-year survival rates [38]. Consequently, to improve long-term survival after colorectal cancer surgery future research should focus on the first 90 days after surgery, as our study indicates that this period of risk is potentially modifiable.…”
Section: Discussionsupporting
confidence: 90%
“…Elderly patients exhibit diverse prognoses based on various morbidities and general conditions. Previous studies have reported lower survival rates among elderly patients after surgery [5,14], however, other studies demonstrated comparable survival outcomes between octogenarians and younger patients [9,15,16]. Octogenarians often present with multiple comorbidities and are susceptible to unpredictable fatal illnesses, making it challenging to establish appropriate comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that elderly patients diagnosed with colorectal cancer have worse outcomes [3][4][5], while others have shown opposite [6][7][8][9]. Moreover, elderly patients are often excluded from clinical trials [10,11], and there is no consistent standard for the age criteria de ning "elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Post-operative 90-day and 180-day survival was 98.1% and 93.1% in patients aged 80 to 90 years old and 98.1% and 88.9% in patients over 90 years old. In another series of 237 octogenarians, the post-operative 90-day mortality was 9.3% [ 22 ]. Factors associated with increased mortality were increasing age, high ASA score, and performance of the operation on an emergency basis.…”
Section: Treatments Of Colorectal Cancers In Octogenarians and Older ...mentioning
confidence: 99%